2007
DOI: 10.4321/s1130-01082007000900007
|View full text |Cite
|
Sign up to set email alerts
|

Punción pancreática ecodirigida: estudio multicéntrico

Abstract: Percutaneous fine-needle aspiration for pancreatic lesions is highly cost-effective and has few and mild complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Results obtained in large series reported in the literature reveal that percutaneous FNA of pancreatic masses present a diagnostic accuracy ranging between 75 and 99.4% [ 28 30 ]. Considering only FNA carried out under US guidance, a diagnostic accuracy ranging between 91 and 99.4% has been reported with sensitivity ranging between 81 and 99.4% [ 28 30 ]. The results of the study carried out by D'Onofrio et al thus compare favorably with the data reported in the literature in terms of sensitivity and diagnostic accuracy (98.7%), but they are obtained in a larger patient population.…”
Section: Invasive Diagnostics/us-guided Needle Aspiration/biopsymentioning
confidence: 99%
“…Results obtained in large series reported in the literature reveal that percutaneous FNA of pancreatic masses present a diagnostic accuracy ranging between 75 and 99.4% [ 28 30 ]. Considering only FNA carried out under US guidance, a diagnostic accuracy ranging between 91 and 99.4% has been reported with sensitivity ranging between 81 and 99.4% [ 28 30 ]. The results of the study carried out by D'Onofrio et al thus compare favorably with the data reported in the literature in terms of sensitivity and diagnostic accuracy (98.7%), but they are obtained in a larger patient population.…”
Section: Invasive Diagnostics/us-guided Needle Aspiration/biopsymentioning
confidence: 99%